Tolerância de Aeromonas spp. ao estresse salino - Visentini, Evanise Oliveski dos Santos (My University, 2014)
The bacteria from the Aeromonas genus are important aquatic microorganisms and causative agents of infectious diseases in animals, and even to mankind. Its wide distribution in continental aquatic and marine environments is an indicative of its ability to adapt to different levels of salinity, which is a relevant fact concerning food contamination. The bacterial tolerance to saline stress is associated with the maintenance of cellular homeostasis through ion transportation systems and the accumulation of organic solutes, such as betaine, proline, among others. Betaine is an osmoprotectant found in plants, animals and microorganisms, transported in bacteria by a transportation system of the ABC specific type, encoded by operon ProU. In this context, the objectives of this study were: to measure the tolerance to saline stress in Aeromonas, including determining the growth and cell viability in Aeromonas in saline stress, evaluate the expression of betaine transport genes after saline stress and create an in silico analysis of the proU operon in Gram negative bacteria. The results demonstrate that Aeromonas trota present more salinity tolerance than Aeromonas hydrophila, and that some Aeromonas species can grow in minimal environment containing up to 0.42 M of NaCl, concentration used as a food preservative agent. The betaine acts as an osmoprotectant in Aeromonas, determining their capacity to survive and grow in higher concentrations of sodium chloride (0.51 to 0.68 M). On the other hand, the choline, considered as an important betaine precursor in some bacteria, presents no osmoprotectant effect on Aeromonas. The evaluation of pre-growth with betaine show that this osmoprotectant is accumulated even in the absence of stress, determining a bacterial pre-adaptation to changes in osmolarity. The in silico analysis of the operon proU, responsible for betaine transportation, shows their high conservation in bacteria, indicating the importance of this ABC transporter. Expression experiments of the operon proU in A. hdydrophila showed constitutive basal expression and significant increase of the operon proU expression in bacteria exposed to osmotic stress, even in the absence of the osmoprotectant. Therefore, the operon proU expression in A. hydrophila is modulated by intracellular stress, in such manner, that it returns to close baseline levels when the cell reaches homeostasis.
As bactérias do gênero Aeromonas são importantes microrganismos aquáticos e agentes causais de doenças infecciosas em animais, inclusive o homem. Sua ampla distribuição em ambientes aquáticos continentais e marinhos é indicativa da sua capacidade de adaptação a distintos níveis de salinidade, fato por sua vez relevante na contaminação de alimentos. A tolerância bacteriana ao estresse salino está associada à manutenção da homeostase celular através de sistemas de transporte de íons e acúmulo de solutos orgânicos, como betaína, prolina, entre outros. A betaína é um osmoprotetor encontrado em plantas, animais e microrganismos sendo transportado em bactérias através de um sistema de transporte do tipo ABC específico codificado pelo operon ProU. Neste contexto, os objetivos deste trabalho foram: avaliar a tolerância ao estresse salino em Aeromonas, incluindo determinar o crescimento e a viabilidade celular em Aeromonas em estresse salino, avaliar a expressão dos genes de transporte de betaína após estresse salino e realizar uma análise in silico do operon proU em bactérias Gram negativas. Os resultados mostram que Aeromonas trota apresenta mais tolerância à salinidade do que Aeromonas hydrophila, sendo que algumas espécies de Aeromonas podem crescer em meio mínimo contendo até 0,42M de NaCl, concentração utilizada como agente de preservação de alimentos. A betaína atua como osmoprotetor em Aeromonas, determinando a sua capacidade de sobrevivência e crescimento em concentrações mais elevadas de cloreto de sódio (0,51 a 0,68M). Por outro lado, a colina, considerada importante precursor da betaína em algumas bactérias, não apresenta efeito osmoprotetor em Aeromonas. Avaliação de pré-crescimento com betaína mostram que este osmoprotetor é acumulado mesmo na ausência de estresse, determinando uma pré-adaptação bacteriana a mudanças de osmolaridade. Análise in silico do operon proU, responsável pelo transporte de betaína, mostra elevada conservação do mesmo em bactérias, indicando a importância deste transportador ABC. Experimentos de expressão do operon proU em A. hdydrophila mostraram expressão constitutiva basal e aumento significativo da expressão do operon proU em bactérias submetidas a estresse osmótico, mesmo na ausência do osmoprotetor. Assim sendo, a expressão do operon proU em A. hydrophila é modulada pelo estresse intracelular, de tal forma que a mesma volta a níveis próximos do basal quando a célula atinge a homeostase.
Keywords: Aeromonas; Biotecnologia; Halotolerance